SWOT Analysis To Determine Competitive Strategy In Yakusa Laundry Business - Arbeiansah Pratama Putra; Surya Ade Saputera; RG Guntur Alam; Yetman Erwadi (Jurnal Komputer, Informasi dan Teknologi, 2024)
In this era of modern development, there is a lot of competition throughout the industrial world, including inside and outside the industry. This also happens because changes in the field of technology are increasingly rapid and precise. In conditions of rapid technological development, this is possible for business actors, especially companies, this situation is no longer surprising when operating in the field of commodity operations, in this case company management will compete with each other through various media to improve the sales process to current marketing consumers. This example is Yakusa Laundry. The author's aim in conducting research on the Yakusa laundry business aims to identify and analyze SWOT, namely strengths, weaknesses, opportunities, threats, such as competitive strategies to increase competitiveness. on the Yakusa Laundry business. This research uses a descriptive qualitative approach, data collection techniques using narrative data methods, namely oral and written interviews, observation and documentation. Investigation of informants is based on relevance and adequacy. The results of research regarding marketing strategies in increasing competitiveness at Yakusa Laundry show an increase in competitiveness, this is proven by the company's control of market share.